2011
DOI: 10.1007/s12010-011-9388-7
|View full text |Cite
|
Sign up to set email alerts
|

Activity and Stability of Chloroperoxidase in the Presence of Small Quantities of Polysaccharides: A Catalytically Favorable Conformation Was Induced

Abstract: Chloroperoxidase (CPO) is thought to be the most versatile heme-containing enzyme with enormous applications in organic synthesis, biotransformation, pharmaceutical production, and detoxification of environmental pollutants. Any improvement in the stability of this enzyme will greatly enhance its application in the mentioned areas. In the present study, the effects of three polysaccharides (soluble starch, β-cyclodextrin, and dextrin) on the stability of CPO at elevated temperatures (20, 30, 35, 40, and 50 °C)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…The same authors had previously reported similar beneficial effects by poly saccharides. 77,78 One of the major limitations of biocatalysis in general lies with the very poor water solubility of many (hydrophobic) reactants of interest. Unfortunately academic researchers tend to circumvent this limitation by adjusting the substrate loading of their reactions to the aqueous solubility of the reagents.…”
Section: Reaction Medium Engineeringmentioning
confidence: 99%
“…The same authors had previously reported similar beneficial effects by poly saccharides. 77,78 One of the major limitations of biocatalysis in general lies with the very poor water solubility of many (hydrophobic) reactants of interest. Unfortunately academic researchers tend to circumvent this limitation by adjusting the substrate loading of their reactions to the aqueous solubility of the reagents.…”
Section: Reaction Medium Engineeringmentioning
confidence: 99%
“…Chloroperoxidase (CPO; E.C. 1.11.1.10), which is a versatile heme-containing enzyme, could catalyze sulfoxidation, epoxidation, dismutation, halogenation, and oxidation of numerous compounds with extensive high regioselectivity and enantioselectivity. , Such excellent catalytic properties enable CPO to have a great potential application in the synthesis of drugs and intermediates, but the lack of long-term operational stability has impeded its feasibility for practical industrial use. , Therefore, it is necessary to develop an effective strategy for improving the stability of CPO. , Immobilization is the most commonly used way to improve the stability of enzyme in industry. Various materials, such as mesoporous silica, organic polymer matrices, , graphene oxide (GO) nanosheets, and nanotubes, , have been selected as supports to facilitate the stability and recycling of immobilized CPO.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 Such excellent catalytic properties enable CPO to have a great potential application in the synthesis of drugs and intermediates, but the lack of long-term operational stability has impeded its feasibility for practical industrial use. 3,4 Therefore, it is necessary to develop an effective strategy for improving the stability of CPO. 5,6 Immobilization is the most commonly used way to improve the stability of enzyme in industry.…”
Section: ■ Introductionmentioning
confidence: 99%